The conception of monopsychism and the realms of man’s being in Enneads by Plotinus - Woszczyk, Agnieszka (Folia Philosophica, 2009)
The paper deals with the relation between the individual soul and the Soul taken as the hypostasis. This relation is the crucial element of Plotinus’ psychology and anthropology. It enables the explanation of the possibility of crossing the connection of a man with his body and finding the beyond-individual realms of being. In this way Plotinus presents various levels of self-knowledge of the self as different levels of its identity, from the level of body and senses, through the noetic dimension, to unio mystica.